Uplift of Shoreline Regions on Pagai Island due to the September 12, 2007 Mw 8.4 Earthquake Captured by SAR Image - Lubis, Ashar Muda (UI Scholars Hub, 2015)
At least 25 people were killed by the September 12, 2007 Mw 8.4 Bengkulu earthquake, and many buildings were destroyed in Bengkulu and West Sumatra provinces. It is very important to estimate the earth surface deformation due to the earthquake to understand the rupture size and its process. The aim of this research is to estimate the shoreline change and vertical displacement on Pagai Island associated with the September 12, 2007 Mw 8.4 Bengkulu earthquake. The intensity of ALOS-PALSAR satellite images is used to access the pattern of displacement. The result shows that Pagai Island demonstrated huge uplift due to the earthquake. In general, the result of uplift in the shoreline regions derived from Synthetic Aperture Radar (SAR) image has a good agreement with other methods, such as in situ measurements, InSAR, and Global Positioning System (GPS) observations. This result implies that the earthquake fault location was very close to/around Pagai Island. Using this method, we can easily estimate the pattern of deformation in very remote and very wide areas without any equipment on the ground. The only limitation is the method cannot provide quantitative displacement.